⎩ ⎪ ⎨ ⎪ ⎧ x 2 + 2 y 2 + 5 z 2 = 3 5 + 6 y z x + 2 y − 3 z = 9 x + y + z = 1 0
Given that the integers ( x , y , z ) are a solution to the following simultaneous equations above, find the value of x y z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Brilliant solution but unfortunately I said "positive integers" by accident. It should've read "Given the integers (x,y,z)" instead.
The question wrote "positive integers" instead of "integers" before this solution was created. Therefore, I would keep the solution for the "positive integers" below the solution for the "integers".
SOLUTION FOR QUESTION IN CURRENT FORM :
We have: ⎩ ⎪ ⎨ ⎪ ⎧ x 2 + 2 y 2 + 5 z 2 = 3 5 + 6 y z x + 2 y − 3 z = 9 x + y + z = 1 0
Subtracting the third equation from the second equation: y − 4 z = − 1
Arranging: y = 4 z − 1
Third equation: x + y + z = 1 0
Substituting y = 4 z − 1 : x + ( 4 z − 1 ) + z = 1 0
Simplifying: x = 1 1 − 5 z
Substituting x = 1 1 − 5 z and y = 4 z − 1 to the first equation: ( 1 1 − 5 z ) 2 + 2 ( 4 z − 1 ) 2 + 5 z 2 = 3 5 + 6 ( 4 z − 1 ) z
Expanding: 1 2 1 − 1 1 0 z + 2 5 z 2 + 3 2 z 2 − 1 6 z + 2 + 5 z 2 = 3 5 + 2 4 z 2 + 6 z
Rearranging and cancelling: 3 8 z 2 − 1 2 0 z + 8 8 = 0
Solving quadratic equation : z = 2 or z = 2 2 1 9
Reject the second one since z is an integer.
Substituting z = 2 to y = 4 z − 1 gives us: y = 4 × 2 − 1 = 7
Substituting z = 2 to x = 1 1 − 5 z gives us: x = 1 1 − 5 × 2 = 1
Therefore: x y z = 1 × 7 × 2 = 1 4
SOLUTION FOR ORIGINAL QUESTION (as reference only):
We have: ⎩ ⎪ ⎨ ⎪ ⎧ x 2 + 2 y 2 + 5 z 2 = 3 5 + 6 y z x + 2 y − 3 z = 9 x + y + z = 1 0
Subtracting the third equation from the second equation: y − 4 z = − 1
Arranging: y = 4 z − 1
From the condition that x ≥ 1 and (z\ge1): y = 1 0 − x − z ≤ 1 0 − 1 − 1 = 8
Therefore, we only have two cases:
Let us plug them into the first equation.
In the first case,
In the second case,
Therefore, x y z = 1 × 7 × 2 = 1 4 .
Brilliant solution but unfortunately I said "positive integers" by accident. It should've read "Given the integers (x,y,z)" instead.
I had to rewrite the question because I forgot I put on the bound "positive integers". It is now written as just "integers". Have a go again if you dare.
I have done it again :D
Problem Loading...
Note Loading...
Set Loading...
Combine 2nd and 3rd equations to get x + 5 z = 1 1 , it follows that z ≤ 2 . Trying z = 1 , 2 gives only one triple with integer values: ( x , y , z ) = ( 1 , 7 , 2 ) .